Identification of Genes in Streptomycin-Resistant pv. Biovar 2 Strains Isolated in Korea - Young Sun Lee; Gyoung Hee Kim; Young Jin Koh; Jae Sung Jung (The Plant Pathology Journal, 2021)
Bacterial canker is a devastating disease of kiwifruit caused by the bacterium Pseudomonas syringe pv. actinidiae. Canker disease of kiwifruit in Korea has been controlled using streptomycin for more than two decades. Four streptomycin-resistant strains, belonging to biovar 2, which are found only in Korea, were collected between 2013 and 2014 from different orchards located in Jeju, Korea. The genetic background for streptomycin resistance among P. syringe pv. actinidiae strains were determined by examining the presence of strA-strB or aadA, which are genes frequently found in streptomycin-resistant bacteria, and a point mutation at codon 43 in the rpsL gene. All four streptomycin-resistant strains of P. syringe pv. actinidiae investigated in this study contained strA-strB as a resistant determinant. The presence of the aadA gene and a mutation in codon 43 of the rpsL gene was not identified.